PENENTUAN DIVIDEND PAYOUT RATIO: BUKTI EMPIRIS PADA PERUSAHAAN LQ 45 DI INDONESIA - Sriyono Sriyono; Andriana Andriana (INVENTORY: JURNAL AKUNTANSI, 2019)
The determination of the dividend payout ratio is a crucial decision in a company, on the company's side must add satau capital for operations while on the other hand the company must retain investors. This research aims to find out what variables affect the stability of the Dividend Payout Ratio on the company's LQ45 listed in Indonesia stock exchange period 2012-2016. Sampling technique used is the method of purposive sampling, data analysis using Technical data analysis panel. The results of this research found a connection between the variable profitability, Leverage, size of company, Earning per share against the Dividend Payout Ratio. Conclusion of this research is the variable size of the influential company profitability and significantly to the stability of the Dividend Payout Ratio, while the Leverage Earning per share is not significant effect against the Dividend Payout Ratio.